PENERAPAN METODE COOPERATIVE LEARNING PADA KEGIATAN ASISTENSI MENGAJAR AKUNTANSI DI SMA PELITA KASIH - Novia, Jessica; Sriwati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Choosing the right learning method is important to increase the students’ enthusiasm and create a pleasant learning atmosphere, especially for subjects that require high concentration and precision such as accounting. Apart from the teacher-centered learning, there is another alternative learning method needed as a complement, namely cooperative-learning method. This method involves dividing a class into small groups who work together, discuss and exchange ideas to solve problems and they are assisted by the teacher. The cooperative-learning method is applied in the teaching assistance program at Pelita Kasih High School, West Jakarta. The aim of using this method is to help students be more active in the learning process, willing to ask if they are facing difficulties, to create a fun and interactive learning atmosphere, and to increase students' understanding academically and socially by helping each other. In conclusion, the approach from the cooperative-learning method is very helpful in learning activities. Students are quite enthusiastic and focus on doing the practice questions given, which may increase their understanding on the accounting subject.